STRATEGI ADVOKASI DALAM KASUS AHOK: PERAN MEDIA SOSIAL DAN PENGARUHNYA TERHADAP OPINI PUBLIK - Khofifah Sekar Ningrum (ADMIN: Jurnal Administrasi Negara, 2025)
This research investigates the advocacy strategies advocacy strategies used in Ahok's controversial case and how the role of social media in social media influenced public opinion regarding the case. The Ahok incident incident involving former Governor of DKI Jakarta Basuki Tjahaja Purnama who was accused of blasphemy has attracted national and international attention in recent years.recent years. Due to its speed and reach, social media played an important role in disseminating information, mobilising supporters and shaping public opinion regarding the incident, and shaping public opinion regarding the incident. This research used a mixed approach, combining social media content analysis with online survey data and interviews with key actors in the advocacy campaign. advocacy campaign. The results show that an intensive and strategic intensive and strategic advocacy campaigns use social media to arouse emotions, amplify advocates' voices, and disseminate messages that mobilise people. the public. However, the role of social media also leads to polarisation, disinformation, and destructive online conflicts. This research provides a detailed description of how Ahok case advocacy groups used social media as a tool to influence public opinion. a tool to influence public opinion. The implications of these findings have implications for our understanding of the dynamics of advocacy campaigns in the digital era and the challenges faced in managing public opinion through social media. dynamics in the digital era and the challenges faced in managing public opinion through social media. social media.